Navigating tourism ethnographies – fieldwork embroiled in time, movement and emotion. Issue 9 (3rd May 2023) - Witte, Alexandra; Wilson, Jase; Burrai, Elisa; Dashper, Kate
ABSTRACT: In this paper, we reflect on the challenges of ethnographic fieldwork in tourism research. Specifically, we discuss the intense, messy and complex dynamics of doing (tourism) ethnographic fieldwork, highlighting how key challenges have affected us as researchers, our practises, relationships and experiences in the field. Our reflections are illustrated considering respectively our research experiences of mountaineering in the Himalayas, walking tourism in China, horse-riding tourism in the UK and volunteer tourism in Peru. Although these fields have very different social and geopolitical contexts, we experienced similar issues. Our most commonly experienced challenges include time limitations, having 'enough data', accessibility to the informants and rapport building. Through the discussion of these challenges, we unpack the often conflicting emotional contours of fieldwork which are commonly experienced but rarely spoken of. With this paper, we seek to open critical debates on the emotional aspects of tourism research which may be particularly useful for novice ethnographers and scholars constrained by the institutionalized pressures of academia.